Diversity and inclusion: biographical experiences and questioning of initial teacher education - Leiva, Roberto; Herrera, Constanza; Núñez, Mauricio; Gallego, Camila (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Initial teacher education is key to inclusive education. However, it is often guided by public policy standards and disconnected from the experiences of its actors. Through a case study of a Chilean Visual Arts Pedagogy program, the educational proposals are questioned based on the biographical experiences of teacher educators and student teachers. It describes aspects not considered in the conception of diversity and inclusion, corporeality, identity, and teacher autonomy. It also outlines possibilities of making sense of the actors’ experiences and orienting their teaching from inclusion.